A celestial motion-based solar photovoltaics installed on a cooling tower. (15th July 2020) - Qi, Lingfei; Jiang, Mingkun; Lv, Yuexia; Yan, Jinyue
Graphical abstract: Highlights: A novel solar photovoltaics (PVs) installed on a cooling tower is first presented. The proposed PVs can reduce land occupation and power loss. Four PVs configurations are compared to estimate the performance. Capacities of the proposed PVs installations reach 1.76 MW, 3.51 MW, and 1.82 MW. Total profits are 27.9 million CNY, 60.7 million CNY, and 36.0 million CNY. Abstract: Traditional photovoltaic systems are facing two major problems, including occupying excessive land resources and causing power loss due to long-distance power transmission. In this paper, we investigate an adaptive celestial motion-based solar photovoltaics, which is installed on the cooling tower of a thermal power plant. The proposed solar photovoltaics can rotate around its own axis and revolve around the cooling tower, which enables the solar panels to be always perpendicular to the solar rays based on the rotation and revolution of the earth. In order to estimate the technical and economic performance of the solar photovoltaics, three thermal power plants located in Wujing, Datong, and Hami in China are selected for a case study. Comparative analysis is conducted under four different photovoltaic configurations of fixed angle, adjustable azimuth, adjustable tilt, and adjustable azimuth and tilt of solar panels. Analysis and estimation results show that the capacities of photovoltaic installations reach 1.76 MW, 3.51 MW, and 1.82 MW, with corresponding annual power generation of 2.13 GWh, 6.00 GWh, and 3.94 GWh in Wujing, Datong, and Hami, respectively. The total profits are 27.9 million CNY, 60.7 million CNY, and 36.0 million CNY, with the return on investment of 240%, 261%, and 300%, respectively. Based on solar radiation, local electricity price, and cooling tower area, the payback period for PVs of the three studied power plants is about 6 years. The high energy and economic benefits indicate that the proposed photovoltaics has a good prospect for being considered as an auxiliary power generation system in thermal power plant.